ANALISIS TENTANG TOLERANSI KEHIDUPAN UMAT BERAGAMA DALAM KONSEP INTEGRASI NASIONAL DI KECAMATAN KEBAKKRAMAT: ANALISIS TENTANG TOLERANSI UMAT BERAGAMA DALAM KONSEP INTEGRASI NASIONAL DI KECAMATAN KEBAKKRAMAT - Alexandrea Tasia Benita Widyasari; Sutoyo, Sutoyo; Trisiana, Anita (Prodi PPKn Universitas Slamet Riyadi, 2023)
The purpose of this research was to find out the life of religious tolerance in the concept of national integration in Kebakkramat; to find out the factors of religious tolerance in the concept of national integration in Kebakkramat; to find out the efforts made in supporting the implementation of religious tolerance in the concept of national integration in Kebakkramat. This research is a qualitative descriptive research with a case study type. This research was conducted at Kebakkramat. The research subjects were sub-district head, PKUB Kebakkramat members and religious leaders. Sources of data used are primary data and secondary data. Data collection is through interviews, observation, and documentation. Test the validity of the data is to use source triangulation and method triangulation. The data analysis technique is through interactive descriptive analysis techniques by means of data collection, data reduction, data display, and drawing conclusions. The results of the study can be concluded that 1) the life of religious tolerance in the concept of national integration has been going well. Religious adherents have carried out their religious teachings well, they tolerate and respect each other; 2) the supporting factor in the realization of inter-religious harmony is the awareness possessed by adherents of religions to carry out their respective religious teachings and religious leaders emphasize each other about religious life in a harmonious community environment. The government fosters a life of religious diversity. The inhibiting factor for tolerance in religious life is spreading things that result in conflict, misunderstandings in inter-religious communication, and a lack of mutual respect in a pluralistic and heterogeneous society; 3) the efforts made in supporting the implementation of tolerance in religious life in the concept of national integration are by maintaining the integrity or diversity among religious adherents, trying to create peace, and avoiding inter-religious conflict. Keywords: Tolerance, National Integration